Topic maintenance in video-mediated virtual exchanges: Rolling the ball back in L2 interactions. (August 2022) - Çimenli, Betül; Sert, Olcay; Jenks, Christopher
Abstract: This study investigates how topics are managed in virtual exchanges between tertiary-level English language learners from Turkey and Kazakhstan. The study reports on a previously unexplored interactional device referred to as "rolling the ball back" (RBB) that invites a co-participant to maintain a current topic of discussion through reciprocation of a question asked previously. Using multimodal conversation analysis, the findings show that RBBs accomplish a range of discursive actions through this reciprocation including requesting for information, asking for opinions, changing speakership, and creating a space for topic extension. RBBs are pedagogically significant and interactionally salient in that "rolling it back" allows students to maintain topic progressivity by asking reciprocating questions in online interaction. These findings contribute to the literature on topic maintenance, as well as existing work concerned with how the discursive organization in virtual exchange can be used to enhance teaching and learning. RBBs can be used by language researchers and practitioners to design new learning practices and materials that facilitate robust learner talk in and out of language classrooms. Highlights: The paper discusses topic maintenance in virtual exchanges between tertiary level L2 learners from Turkey and Kazakhstan. Rolling-the-ball-back (RBB) is an interactional device for managing topic maintenance in online L2 talk. RBB extends opportunities for L2 use in interaction as it reciprocates topic proffering questions while changing speakership. RBB can contribute to the development of interactional competence and can inform task design and L2 teaching practices.